Urban green infrastructure index: Assessing supply of regulating and cultural ecosystem services at a megacity scale - Yury Dvornikov; Valentina Grigorieva; Vyacheslav Vasenev; Mikhail Varentsov; Olga Romzaykina; Olga Maximova; Anastasia Konstantinova; Victor Matasov; Ekaterina Kozlova (Ecological Indicators)
Urban green infrastructures (UGI) contribute to a quality of life in cities by provisioning cultural and regulating ecosystem services (ES). Planning and management of UGI needs transparent and spatially explicit indicators of the ES supply. In this study, we have used open-source geospatial data to quantify regulating (air pollution/noise and stormwater runoff regulation, climate mitigation), and cultural (aesthetic values, recreational activities, observation of flora and fauna) ES at three spatial levels within the Moscow megacity (municipal areas (districts), residential areas (quarters), and regular grid). For five regulating and two cultural ES we have developed six physically measurable indicators directly related to potential ES supply and an aggregated UGI index to reflect the cumulative impact of the investigated ES. The proposed UGI index has several important advantages: 1) it considers multiple scales; 2) it relies on CICES classification of ES, including regulating and cultural services; and 3) it is mainly based on open data sources. The developed approach allowed to explore spatial variation in UGI ES and to identify hotspots on the city map where these ES were undersupplied. The outcomes were verified thought comparison with other indices and rankings existing for Moscow. The revealed spatial disparity in UGI ES supply in the Moscow megacity (e.g., differences between central districts and suburbs or neighborhoods with higher and lower accessibility of the nearest urban forest) challenges the city’s environmental strategy, which aims to provide an equal access to green spaces for all citizens. To achieve this goal, several measures were proposed to reach at least half of the potential ES supply at the level of areal units.